The Velvet Revolution In Armenia In The Perspective Of Hannah Arendt’s Political Theory - Nedolyan, Henrik (NAS RA)
This research paper critically analyzes the 2018 Armenian Velvet Revolution, examining its non-violent nature and impact on society. This paper is written largely on the basis of my master’s thesis at the European University in St. Petersburg, which I defended in 2023. The paper consists of two parts. The first part is devoted to the events preceding the Velvet Revolution in Armenia and is written primarily from the perspective of the history of public protests in Armenia. The second part contains reflections on the revolution from the perspective of Hannah Arendt’s philosophy and political theory.
Keywords: Political Philosophy